Analysis of Technology Acceptance Model for Implementation of Sustainable Construction Water Resources Project in Kediri City - Sony Susanto; Winarto, Sigit; Mahardana, Zendy Bima (CIVED, 2024)
Water resource projects in Kediri include various initiatives aimed at improving the quality of life of the community and preserving the environment. This study identifies factors that influence the acceptance of environmentally friendly technologies in sustainable water resource projects in Kediri City, such as the construction of Embung Kalipang, Ngrayut, Dhoho Airport, water source conservation in Sumber Dadapan, and the development of Sumber Banteng. The installation of Automatic Water Level Recorder (AWLR) also helps in real-time monitoring of water levels for flood mitigation. Using the Technology Acceptance Model (TAM) approach, this study analyzes two main variables, namely perceived ease of use (PEOU) and perceived usefulness (PU) of green technology. The survey data collected were analyzed using the Partial Least Squares (PLS) method, which revealed that perceptions of ease of use and benefits of technology influence attitudes and intentions to adopt technology in construction. Although the potential for adoption is high, challenges such as lack of knowledge and implementation costs are major barriers. These findings provide insights for formulating policies that support the implementation of environmentally friendly technologies and become the basis for developing sustainable projects in Kediri in the future.